Programming language pragmatics - Scott, Michael Lee, 1959- (Elsevier/Morgan Kaufmann Pub., 2009)
Programming Language Pragmatics is the most comprehensive programming language textbook available today. Taking the perspective that language design and language implementation are tightly interconnected, and that neither can be fully understood in isolation, this critically acclaimed and bestselling book has been thoroughly updated to cover the most recent developments in programming language design. With a new chapter on run-time program management and expanded coverage of concurrency, this new edition provides both students and professionals alike with a solid understanding of the most important issues driving software development today. Classic programming foundations text now updated to familiarize students with the languages they are most likely to encounter in the workforce, including including Java 7, C++, C# 3.0, F♯, Fortran 2008, Ada 2005, Scheme R6RS, and Perl 6.New and expanded coverage of concurrency and run-time systems ensures students and professionals understand the most important advances driving software today.Includes over 800 numbered examples to help the reader quickly cross-reference and access content.